The TV crime drama - Turnbull, Sue, 1950- (TV genres., 2014)
Maps the development of the crime drama on international television. As a genre, the television crime drama has long been a constant of the television landscape since it first migrated from film and radio onto the small screen in the 1950s. Since then, from Dixon of Dock Green to The Wire, from Minder to The Sopranos or Cracker to Dexter and The Killing, it has continued to attract large audiences even as the depiction of the crime, the perpetrators and the investigators may have changed. In order to track these changes, this book provides an historical analysis of the TV crime series as a genre by paying close attention not only to the nature of TV dramas themselves, but also to the context of production and reception. Rather than simply providing an overview, this book offers a series of case studies to illuminate key issues in the trajectory of the genre. Particular attention will be paid to the transnational career of the television crime drama, including the British and American product, as well as attention to crime drama series produced in other national contexts such as Europe and Australia. In terms of reception, this book includes original research on how the TV crime drama is perceived by audiences within the particular national context of Australia where American, British and European crime dramas vie for attention in the TV schedule alongside the local product. Finally, the future of the TV crime series is canvassed in a discussion of the changing television landscape and the shift to other forms of TV consumption enabled by new digital technologies.